Early Goal Directed Training vs Passive Therapy for Functional Independence of Infants with Cerebral Palsy: Systematic Review and Meta Analysis - Tricia Arella Taslim; Dhana Carissa Wangjaya; Deyra Maheswari Wistara; Febry Liana; Fadhlurrahman Ahmad Ariq Bachtiar (Journal of Asian Medical Students' Association, 2026)
Background: Cerebral palsy (CP) is the leading cause of childhood motor disability, especially in LMICs. Early intervention is critical, yet the efficacy of goal-directed training compared to passive/standard therapies remains debated. Objective: This study aims to evaluate the effectiveness of early goal-directed interventions on improving functional independence in infants and children with or at high risk of CP. Methods: This systematic review and meta-analysis were conducted in accordance with PRISMA guidelines. A comprehensive literature search was performed to identify randomized controlled trials (RCTs) comparing goal-directed training with passive therapy or standard care. Methodological quality was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool. Data were synthesized using a random-effects model to calculate the Standardized Mean Difference (SMD). Results: Five RCTs involving 302 participants were included. Meta-analysis revealed that goal-directed training showed a positive trend toward improved functional outcomes compared to passive therapy, although it did not reach statistical significance (SMD 0.19; 95% CI -0.09 to 0.47; p=0.1398). Heterogeneity across studies was remarkably low (I2 = 0), indicating a consistent intervention effect across diverse age groups and therapeutic modalities. Risk of bias assessment identified "some concerns" in three studies primarily due to missing outcome data, while two trials were rated as low risk. Conclusion: Goal-directed training demonstrates a promising and consistent clinical trend in enhancing functional independence for children with CP. Despite the current lack of statistical significance, the negligible heterogeneity supports the integration of active, goal-focused exercises as a potentially effective and stable strategy for early neurorehabilitation.